1995
DOI: 10.1074/jbc.270.20.11789
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Interaction of Y1-Neuropeptide Y and α1b-Adrenergic Receptors in the Regulation of Phospholipase C, Protein Kinase C, and Arachidonic Acid Production

Abstract: Neuropeptide Y (NPY) and norepinephrine, found colocalized in sympathetic neurons innervating blood vessels, exert synergistic responses on vasoconstriction. To examine the signaling mechanisms involved, free of complications associated with mixed receptor populations, we have established a stable Chinese hamster ovary cell line expressing both Y1-NPY and alpha 1b-adrenergic receptors. Occupation of either receptor species, with 100 nM peptide YY (PYY) or 10 microM phenylephrine (PE), respectively, resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
103
4

Year Published

1995
1995
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(117 citation statements)
references
References 46 publications
10
103
4
Order By: Relevance
“…PKC-is the main novel isozyme expressed in skeletal muscle, testes, platelets, and their megakaryoblastic precursor cells, T-lymphocytes, and neoplastic hemopoietic cells (7,48,49). We have found moesin phosphorylation activity in HL-60 cells, spleen cells, and AML cells, which is consistent with the known distribution of PKC- (29) and in contrast to the tissue distribution of the (50) and the / isoforms, which are not found in spleen (51,52). We have previously described modulation of this activity under various conditions affecting cellular proliferation and differentiation (4,5).…”
Section: Discussionsupporting
confidence: 34%
“…PKC-is the main novel isozyme expressed in skeletal muscle, testes, platelets, and their megakaryoblastic precursor cells, T-lymphocytes, and neoplastic hemopoietic cells (7,48,49). We have found moesin phosphorylation activity in HL-60 cells, spleen cells, and AML cells, which is consistent with the known distribution of PKC- (29) and in contrast to the tissue distribution of the (50) and the / isoforms, which are not found in spleen (51,52). We have previously described modulation of this activity under various conditions affecting cellular proliferation and differentiation (4,5).…”
Section: Discussionsupporting
confidence: 34%
“…For this reason this peptide was chosen to raise PKC [-specific antibodies by Gibco and several authors, and used by many groups to determine the presence of this isoform in human [7-91 and other species [lo-171. Very recently, it has been reported that this antipeptide antibody also recognizes a newly described PKC, aPKCz [4]. This isoform is clearly different from the 77 kDa cPKC since it has a lower molecular weight and does not respond to TPA or Ca2' [4].…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, it has been reported that this antipeptide antibody also recognizes a newly described PKC, aPKCz [4]. This isoform is clearly different from the 77 kDa cPKC since it has a lower molecular weight and does not respond to TPA or Ca2' [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the conventional PKC isoforms (c&r) are activated by calcium, PS, and DAG or PDBu. The novel PKC isoforms (6,~,rl,t3) are also activated by PS and DAG or PDBu but lack the calcium binding domain, whereas atypical PKC isoforms (&t,y,u) are activated by PS but not by DAG, PDBu, or calcium [9,20,21]. Very little is known about the distribution and expression of PKC isoforms in vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%